American Indian stories, legends, and other writings - Zitkala-Sa, 1876-1938.; Davidson, Cathy N., 1949-; Norris, Ada. (New York, N.Y. : Penguin Books, 2003)
When first published in 1899, charges of sordidness and immorality consigned The Awakening into initial obscurity and irreparably damaged its author's literary and social reputation. In her introduction, Sandra M. Gilbert considers the issues explored in the novel and the stories from their growth out of the feminist literary tradition of the nineteenth century to their place among other concerns of fin de sicle writers in America and England.
Old Indian legends -- American Indian stories -- Selections from American Indian magazine -- Poetry, pamphlets, essays, and speeches.
Includes bibliographical references.
Keywords: Indians of North America -- Folklore; Indians of North America -- Social conditions; Speeches, addresses, etc., Indian -- United States; Legends -- United States